2014
DOI: 10.1071/sr14008
|View full text |Cite
|
Sign up to set email alerts
|

Climate factors mediate soil respiration dynamics in Mediterranean agricultural environments: an empirical approach

Abstract: Soil CO2 emissions, the result of soil respiration processes, may be essential in climate change modelling. The complex phenomenon of soil respiration is regulated by a range of mainly climate-related environmental factors. We tested the latest published empirical models in a field experiment in an agricultural soil under Mediterranean conditions. Soil respiration was monitored biweekly with a portable infrared gas analyser, and climate features were monitored for 1 year (2010–11). An additional rewetting assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…The application of our modified Martin and Bolstad model suggested that in CONT soils the interaction of Ts and Ms modulated Rs, as in our previous experiment (González-Ubierna et al, 2014). BOR application modified the relative importance of the interaction between these climate variables, and the single effect of Ts was the main driver of Rs, while Ms modulated the response, as suggested by Fang and Moncrieff (2001) and Almagro et al (2009).…”
Section: Synergic Effectsmentioning
confidence: 82%
See 2 more Smart Citations
“…The application of our modified Martin and Bolstad model suggested that in CONT soils the interaction of Ts and Ms modulated Rs, as in our previous experiment (González-Ubierna et al, 2014). BOR application modified the relative importance of the interaction between these climate variables, and the single effect of Ts was the main driver of Rs, while Ms modulated the response, as suggested by Fang and Moncrieff (2001) and Almagro et al (2009).…”
Section: Synergic Effectsmentioning
confidence: 82%
“…In González-Ubierna et al (2014) we found the Gaussian model to be the best approach for expressing single relationships between soil climate variables (temperature, moisture or RWi) and soil respiration. We also devised a modification of Martin and Bolstad's model (Martin and Bolstad, 2009) to include all these variables in a single expression:…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to the fitted empirical equations in Tables 2 and 3, our findings indicated that the soil temperature and water content combination had a significant impact on the RS (p < 0.01). However, at the seasonal scale the www.nature.com/scientificreports/ percentages of the variance that were explained by the two-variable models were 44% at the CK site, 43% at the CT site, and 41% at the WM site (Table 3), indicating that the soil temperature and water content may not be the dominant influential factors in the study and that there are still some possible factors that impact the RS 54 . Schütt et al 55 found that, although the temperature and water content at the soil surface are the primary factors restricting RS, especially in low temperature environments, other environmental factors (such as low SOC and high soil salt) become the limiting factors when the temperature is suitable for root and microbe respiration.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the accumulation of carbon exudates in roots as well as variation in canopy transpiration and shading through the phenological cycle creates local soil conditions modifying heterotrophic respiration processes [19]. In agricultural fields all these factors result in a high CO 2 fluxes spatial and temporal variability [20,21] which may be stronger in rainfed crops in Mediterranean climates due to the irregular distribution of rainfall and temperature [22,23].…”
Section: Introductionmentioning
confidence: 99%